Environmental non-migration as adaptation in hazard-prone areas: Evidence from coastal Bangladesh - Khatun, Fatema; Ahsan, Md. Nasif; Afrin, Sonia; Warner, Jeroen; Ahsan, Reazul; Mallick, Bishawjit; Kumar, Pankaj (Elsevier, 2024)
This article was published in The Global Environmental Change [©2022 Rights managed by Elsevier] and the definite version is available at: https://doi.org/10.1016/j.gloenvcha.2022.102610 Get rights and content The Article's website is at: https://www.sciencedirect.com/science/article/abs/pii/S0959378022001480?via%3Dihub